Contemporary accuracy of death certificates for coding prostate cancer as a cause of death: Is reliance on death certification good enough? A comparison with blinded review by an independent cause of death evaluation committee - Turner, Emma L; Metcalfe, Chris; Donovan, Jenny L; Noble, Sian; Sterne, Jonathan A C; Lane, J Athene; I Walsh, Eleanor; Hill, Elizabeth M; Down, Liz; Ben-Shlomo, Yoav; Oliver, Steven E; Evans, Simon; et al. (British journal of cancer, 2016)
Background: Accurate cause of death assignment is crucial for prostate cancer epidemiology and trials reporting prostate cancer-specific mortality outcomes. Methods: We compared death certificate information with independent cause of death evaluation by an expert committee within a prostate cancer trial (2002–2015). Results: Of 1236 deaths assessed, expert committee evaluation attributed 523 (42%) to prostate cancer, agreeing with death certificate cause of death in 1134 cases (92%, 95% CI: 90%, 93%). The sensitivity of death certificates in identifying prostate cancer deaths as classified by the committee was 91% (95% CI: 89%, 94%); specificity was 92% (95% CI: 90%, 94%). Sensitivity and specificity were lower where death occurred within 1 year of diagnosis, and where there was another primary cancer diagnosis. Conclusions: UK death certificates accurately identify cause of death in men with prostate cancer, supporting their use in routine statistics. Possible differential misattribution by trial arm supports independent evaluation in randomised trials.